Přechod k mateřství – plány versus realita týkající se pracovních životů vysokoškolsky vzdělaných žen - Olga Nešporová (Gender a Výzkum)
The article provides a detailed insight into a critical stage in the life course of young women. It focuses on the transition to first-time motherhood among women with tertiary education in heterosexual dual-earner couples in the Czech Republic. The plans of pregnant women regarding their working lives following the birth of their first child are compared with the subsequent realities of their lives (the first eighteen months of their motherhood). The study is based on longitudinal qualitative research conducted between 2011 and 2014. The research revealed that pregnant women did not consider motherhood and paid work as contradictory and that most of them anticipated working before their child´s third birthday. Due to the reality of motherhood and the chances of combining childcare and work, a number of the women in the sample changed their plans, did not return to work once their children reached eighteen months of age and did not expect to return to work in the near future. The lack of available non-maternal childcare or the unwillingness to take advantage of it were found to be the key factors in their decision not to work, coupled with a shortage of part-time work and flexible working arrangements (working hours and place of work). Conversely, the offer of flexible working conditions, the prospect of good financial rewards and a positive relationship between the woman and her work constituted the key reasons for women to return to work during the first eighteen months of their child’s age. With regard to the fulfilment of their plans, structural conditions and constraints were identified as being of greater importance than personal preferences.